P16.29 Prevalence of metabolic risk factors in hiv-infected population under antiretroviral therapy in northern malawi. (13th September 2015) - Chung, CC; Lin, HH; Mtika, CC; Wu, J
Abstract : Introduction: With increased availability of antiretroviral therapy (ART), the life expectancy of people with human immunodeficiency virus (HIV) infection is expected to improve substantially. On the other hand, life-long ART may be associated with increased obesity, diabetes, and hypertension. The situation of obesity, diabetes, and hypertension in HIV-infected population in Malawi is unclear. Methods: We conducted a cross-sectional study including adult HIV-infected patients under ART treatment in a teaching hospital from northern Malawi. Trained field workers performed anthropometric measurements, blood pressure exam, and finger prick test for blood glucose. We followed the WHO and International Diabetes Federation (IDF) criteria to define obesity, hypertension, and diabetes. We compared the prevalence of metabolic risk factors in our study population to that in the 2009 STEPwise approach to Surveillance (STEPS) survey in Malawi. Results: The study included 410 participants (20.97% males). The prevalence of overweight (25≤BMI <30) and obesity (BMI ≥30) was 22.9% (95% CI: 18.9–26.9%) and 10.0% (95% CI: 7.1–12.9%), respectively. The prevalence was higher than that in the STEPS survey (21.9% for overweight and 4.6% for obesity). Notably the situation of overweight and obesity was much worse in females (26.8% and 12.3%) than in males (8.2% and 1.2%). Old age (OR: 1.064 per year, p = 0.0016) and alcohol drinking (OR: 7.309, p = 0.0005) were significant associated with obesity. The prevalence of diabetes or impaired fasting glucose (20.2%, 95% CI: 16.3–24.1%) was higher than that in STEPS survey (9.8%). The overall prevalence of hypertension was 18.1% (95% CI: 14.3–21.8%), lower than that in the STEPS survey (32.9%). Conclusion: Our study provides an initial assessment of the burden of metabolic risk factors among HIV-infected population under long-term ART treatment in Malawi. The high prevalence of metabolic risk factors in this population is concerning. Long-term impact on the burden of noncommunicable diseases warrants further investigation. Disclosure of interest statement: This study was funded by Luke international belongs Pingtung Christian hospital. And that was leaded by National Taiwan University for academic research.